Improving Intergroup Relations with Extended Contact among Young Children: Mediation by Intergroup Empathy and Moderation by Direct Intergroup Contact. (16th November 2016) - Vezzali, Loris; Hewstone, Miles; Capozza, Dora; Trifiletti, Elena; Bernardo, Gian Antonio Di
Abstract: A correlational study investigated extended contact as a strategy to improve outgroup attitudes and stereotyping and to prepare children for future contact. Additional aims were to investigate when and why the effects of extended contact occur. In particular, intergroup empathy was tested as a mediator and direct contact (i.e. cross‐group friendship) as a moderator of extended contact. Participants were Italian and immigrant elementary school children. Results showed that extended contact was associated with improved intergroup empathy, which, in turn, was associated with more positive outgroup attitudes, stereotypes and behavioural intentions. These effects were significant only among participants with a low or moderate level of direct contact. The theoretical and practical implications of findings are discussed. Copyright © 2016 John Wiley & Sons, Ltd.